THE COMPARISON OF SIMPLE ADDITIVE WEIGHTING AND TOPSIS TO MEASURE THE PERFORMANCE OF THE VILLAGE HEAD IN PRINGSEWU REGENCY - Andreas Andoyo; Riki Renaldo; Siti Mukodimah; Yuntriani Yuntriani (Bakti Nusantara Institute, 2020)
The village has an important role in improving the national economy. A developed village will have a good impact on people's lives, both from the economy and the welfare of the community. The village head has an important role in running the government in rural areas. One of the indicators for evaluating the success rate of development and prosperity of an area is the success of a village itself so that the village or village has an important role in the process of improving development. With special autonomy regarding village development, the role of the village head becomes central and becomes the driving force for village development. To find out how well the village head is performing, it is necessary to have a breakthrough in measuring the village head's performance index in Pringsewu Regency. In measuring the performance of the Village Head, the criteria and weighting of the Simple Additive Weighting and TOPSIS methods are used. The sample was tested using eighteen villages spread across nine sub regency in the Pringsewu Regency. The application of two methods of decision support systems using Simple Additive Weighting and TOPSIS in measuring the index of Village Heads in Pringsewu Regency can trigger an increase in the performance of village heads to build the villages based on predetermined criteria. Of the eighteen alternatives tested, the highest value was A16 with a value of 0.8901508.